The Social Distribution of Moxie: The Legacy of Christine Sleeter - Ginsburg, Faye; Rapp, Rayna (Disability Studies Quarterly, 2010)
<!–[if gte mso 9]> 72 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> As anthropologists studying the current landscape of learning disabilities in New York City, we are deeply indebted to Sleeter’s critical insights into both the contemporary moment and the highly stratified historical conditions that produced the intense concern with literacy and academic achievement in a post-war labor market that required escalating white-collar skills. The map of the LD world has become more complex since 1987 due to a number of developments: (1) the increased survival rate of medically challenged infants and children who remain with their families rather than being removed to institutions, eventually requiring a "free and appropriate education"; (2) the wide acceptance of new scientific explanations provided by neuroscience and genetics with attendant notions of intervention; (3) the expanding coverage providing by legislation concerning the educational rights of those with disabilities from the periodic renewals of the IDEA, the passage of the ADA, followed by a series of groundbreaking Supreme Court cases notably Nickerson and Carter; and (4) the growth of curricular innovation to address different learning styles in both the public and private sectors, in an effort to address and destigmatize the presence of "all kinds of minds" in American classrooms. While Sleeter identified the role of family activists in stratifying the kinds of categories assigned to children’s learning differences, our research with NYC parents of children with IEPs in the 21st century highlights the immense amount of social labor required to stabilize and utilize the category across class and race lines. Notably, this work is carried out by mothers who often become advocates for their children in order to get the services to which they are entitled, but which often disappear unless a parent secures them.